The intentionality of the poetic discourse is an application to examples of the Iraqi prose poem - Abdel Rasoul, Alia Saadi (Al-Adab Journal, 2015)
the language Generate new human relations spin in molar displacement to generate its point of view , and poetry is the most capable model to break the routine in terms of deeper limp in its regards over the prose poem ; it painted language through pictures swim in its freedom, to divide the search then to three departments :The first department : the formalization : it is a certain development core of a positive or negative aspect , without paying attention to the repetition of certain linguistic unit base, but is about the birth of a new meaning .The second department : Interactive: confined to the mutual influence between Narrator and receiver in different systemic messages .The third department : talk: flexibility in the expression of the idea of the different points of view multiple votes where flexible ideology